Obecność anioła w opowiadaniu o najeździe Sennacheryba na Jerozolimę w Syr 48,21 - Pudełko, Judyta (The Biblical Annals, 2019)
Biblical books, while presenting events from the history of biblical Israel, interpret them in a theological manner. This principle also applies to the description of Sennacherib’s military campaign against Judah and Jerusalem in 701 BC. This campaign is even reported in the Assyrian sources, which underline Assyrian military power. The biblical narrative emphasizes an extraordinary intervention of God, who saves his people in a mysterious way. This divine intervention was so important that is was reported in the Old Testament writings four times (2 Kgs 19:35; 2 Chr 32:21; Is 37:21; Sirach 48:21). Biblical reports explains the rescue of Jerusalem by the intervention of God, who is acting by his “messenger” – an angel. In the latest description of this event, found in Ben Sira 47:21H, the sage from Jerusalem gives his own interpretation of the whole affair, which differs slightly from other reports. The angel, by whom God is acting, is identified with the prophet Isaiah, who announces the salvage of Jerusalem as an answer to people’s prayers.